Effectiveness and safety of non-pharmacological therapies for the treatment of inflammatory bowel disease: a network meta-analysis - Jia, Jing; Wu, Yun-bo; Liu, Si-wei; Chen, Wei-jing; Li, Ru-liu; Bai, Yun-long; Hu, Ling (Frontiers in Medicine, 2025)
BackgroundInflammatory bowel disease (IBD), encompassing both Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic, inflammatory, and immune-mediated disorder of the gastrointestinal tract. If left inadequately treated, IBD can lead to disease progression, resulting in severe long-term complications, including irreversible structural damage to the intestinal tissues. While clinical symptoms are traditionally used to assess treatment efficacy, they do not always align with the underlying mucosal inflammation, particularly in CD. This limitation underscores the importance of exploring alternative treatment strategies. To address this gap, the present study evaluates the effectiveness of non-pharmacological treatments (NPTs) for IBD through a network meta-analysis (NMA), providing a thorough assessment of the available evidence.MethodsWe systematically reviewed randomized controlled trials (RCTs) from the following databases: PubMed, Embase, Springer, Cochrane Controlled Register of Trials (CENTRAL), and Web of Science, comparing various NPTs for IBD, including Cognitive Behavioral Therapy (CBT), diet interventions (DI), fecal microbiota transplantation (FMT), physical training (PT), and acupuncture and moxibustion (APMX). Outcomes assessed included clinical remission, disease activity, quality of life (QOL), serum biomarkers (fecal calprotectin [FC] and C-reactive protein [CRP]), and adverse effects. The quality assessment was assessed by Cochrane Handbook and GRADEpro software. The risk ratio (RR) was calculated for dichotomous outcomes while standardized mean difference (SMD) was used for continuous variables with 95% credible intervals (CI). Funnel plot was performed to evaluate publication bias. Surface under the cumulative ranking curve (SUCRA) was conducted to rank the included interventions. Data were analyzed with STATA 15.0 and Review Manager 5.3.ResultsA total of 62 eligible RCTs were identified in this NMA. The results showed that standard medical therapy (SMT) exhibited the highest probability in inducing clinical remission, as expected. Among non-pharmacological interventions, APMX, a traditional Chinese medicine involving acupuncture and moxibustion, showed promising results in both animal models and clinical trials, reducing serum TNF-α levels and improving intestinal health. DI was most effective in maintaining clinical remission and reducing serum FC levels. FMT emerged as the most effective treatment for reducing serum CRP levels and ranked second in terms of clinical remission induction.ConclusionAPMX, DI, and FMT represent promising non-pharmacological options for managing IBD. APMX was the most effective for clinical remission and symptom relief, while DI was best for maintaining remission, and FMT showed promise in reducing inflammation. Further high-quality clinical trials are needed to strengthen the evidence and guide clinical practice in IBD management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024596233, CRD42024596233.